2011
DOI: 10.2214/ajr.10.5920
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Finding of Renal Masses at Unenhanced CT: Prevalence and Analysis of Features for Guiding Management

Abstract: The incidental finding of a renal mass is relatively common at unenhanced CT, but imaging criteria can be used for reliable identification of most of these lesions as benign without further workup. Mean attenuation alone appears reliable for determining which renal masses need further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(77 citation statements)
references
References 26 publications
3
72
0
2
Order By: Relevance
“…Twenty-one studies (n = 38 293) (References 45, 85, 99, 101, 125, 127, 134, 137-139, 141, 150, 152, 160, 164, 166-168, 184, 195, 198) in 22 articles (References 45,85,99,101,114,125,127,134,(137)(138)(139)141,150,152,160,164,(166)(167)(168)184,195,198) (7 studies with overlapping populations reported different types extracolonic findings) reported on extracolonic findings in asymptomatic persons (eTable 5 in the Supplement). In general, these studies varied greatly in their ability to accurately assess follow-up and the duration of follow-up.…”
Section: Ctc Extracolonic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies (n = 38 293) (References 45, 85, 99, 101, 125, 127, 134, 137-139, 141, 150, 152, 160, 164, 166-168, 184, 195, 198) in 22 articles (References 45,85,99,101,114,125,127,134,(137)(138)(139)141,150,152,160,164,(166)(167)(168)184,195,198) (7 studies with overlapping populations reported different types extracolonic findings) reported on extracolonic findings in asymptomatic persons (eTable 5 in the Supplement). In general, these studies varied greatly in their ability to accurately assess follow-up and the duration of follow-up.…”
Section: Ctc Extracolonic Findingsmentioning
confidence: 99%
“…7 This study's population overlapped with several already included studies and reported that 2.5% of examinations had E4 category findings, consistent with findings from included studies. 150,164,[166][167][168]195,198 Discussion Colorectal cancer screening continues to be a necessary and active field of research. Since the 2008 USPSTF recommendation was published, 95 new studies were identified, including more evidence on (1) the effectiveness of SIG for reducing CRC mortality, (2) the test performance of screening CTC and decreasing radiation exposure from CTC, and (3) the test performance of a number of FDAapproved FITs (including 1 FIT plus sDNA test).…”
Section: Ctc Extracolonic Findingsmentioning
confidence: 99%
“…Data available about the frequency of incidental findings in the abdomen derive from CT examinations performed in a search for renal calculi with low-dose CT, CT colonography for cancer screening, emergency CT in trauma patients, and CTA of the abdominal aorta and the lower extremities (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Messersmith et al, evaluating 321 consecutive patients from the emergency department with non-contrast renal stone abdominal scans, found a 45% prevalence of incidental findings (half were rated of ''moderate or serious'' concern), however, they did not report on any malignancies (17 (28).…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating 3000 patients undergoing computed tomography (CT) for screening colonography, 14% were found to have an incidental renal lesion >1 cm [1]. Overall, up to 66% of the small renal masses <4 cm are incidentally found [2].…”
Section: Introductionmentioning
confidence: 99%